Targeting the Highly Conserved 3' Untranslated Region of Iris Severe Mosaic Virus for Sensitive Monitoring of the Disease Prevalence in Iris Production - Grunwald, Derrick J (Plant disease, 2023)
Iris severe mosaic virus (ISMV, Potyviridae) can threaten the sustainability of iris production and the marketability of the plants. Effective intervention and control strategies require rapid and early detection of viral infections. The wide range of viral symptoms, from asymptomatic to severe chlorosis of the leaves, renders diagnosis solely based on visual indicators ineffective. A nested PCR-based diagnostic assay was developed for the reliable detection of ISMV in iris leaves and in rhizomes. Considering the genetic variability of ISMV, two primer pairs were designed to detect the highly conserved 3' untranslated region (UTR) of the viral genomic RNA. The specificity of the primer pairs was confirmed against four other potyviruses. The sensitivity of detection was enhanced by one order of magnitude using diluted cDNA and a nested approach. Nested PCR facilitated detecting ISMV on field-grown samples beyond the capabilities of a currently available immunological test and in iris rhizome, which would facilitate ensuring clean stock is planted. This approach dramatically improves the detection threshold of ISMV on potentially low virus titer samples. The study provides a practical, accurate, and sensitive tool for the early detection of a deleterious virus that infects a popular ornamental and landscape plant